Enhancing Mitofusin/Marf ameliorates neuromuscular dysfunction in Drosophila models of TDP-43 proteinopathies. - Khalil, B.; Cabirol-Pol, M.J.; Miguel, L.; Whitworth, A.J.; Lecourtois, M.; Liévens, J.C. (Neurobiology of Aging, 2017)
Transactive response DNA-binding protein 43 kDa (TDP-43) is considered a major pathological protein in amyotrophic lateral sclerosis and frontotemporal lobar degeneration. The precise mechanisms by which TDP-43 dysregulation leads to toxicity in neurons are not fully understood. Using TDP-43-expressing Drosophila, we examined whether mitochondrial dysfunction is a central determinant in TDP-43 pathogenesis. Expression of human wild-type TDP-43 in Drosophila neurons results in abnormally small mitochondria. The mitochondrial fragmentation is correlated with a specific decrease in the mRNA and protein levels of the Drosophila profusion gene mitofusin/marf. Importantly, overexpression of Marf ameliorates defects in spontaneous walking activity and startle-induced climbing response of TDP-43-expressing flies. Partial inactivation of the mitochondrial profission factor, dynamin-related protein 1, also mitigates TDP-43-induced locomotor deficits. Expression of TDP-43 impairs neuromuscular junction transmission upon repetitive stimulation of the giant fiber circuit that controls flight muscles, which is also ameliorated by Marf overexpression. We show here for the first time that enhancing the profusion gene mitofusin/marf is beneficial in an in vivo model of TDP-43 proteinopathies, serving as a potential therapeutic target.